(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Vitiligo is an acquired hypomelanotic pigmentary disorder characterized by depigmented macules in the skin due to loss of melanocyte functions. The study aimed to detect levels of IL-10, IL-6, and IFN-ɤ. The study included 50 patients with an age range between 8 and 63 years, 27 males and 23 females, and 40 apparently healthy controls (20 males and 20 females). Serum was separated, and levels of cytokines above were detected by using enzyme-linked immunosorbent assay (ELISA). The results showed the average age of patients was 26.920 years, and the 10-20 age group had a higher percentage of infection with vitiligo (46%), while the less than 10 years age group had 4%. Family history positivity was 32%, and results according to distribution of vitiligo lesion were generalized (56%), localized (35%), and universal (10%). The results of the mean level of IL-10 showed a significant reduction (P < 0.001) compared with the healthy control, and the mean levels of IL-6 showed a non-significant increase (P ≥ 0.05), while the mean levels of IFN-ɤ showed a significant increase (P ≤ 0.05). From these findings, we can conclude that marked low serum levels of IL-10 and high serum levels of IFN-ɤ and IL-6 in vitiligo patients clarify their important participation in the pathogenesis of vitiligo.